Respuesta :

Option A:

Yes, he is correct.

Solution:

To find the distance between two points (2, 4) and (6, 3).

Distance between two points formula:

[tex]d=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}[/tex]

Here [tex]x_1=2, x_2=6, y_1=4, y_2=3[/tex]

Substitute these in the distance formula.

Step 1:

[tex]d=\sqrt{(6-2)^2+(3-4)^2}[/tex]

Step 2 :

Using BODMAS rule, first simplify the values into the bracket.

[tex]d=\sqrt{(4)^2+(-1)^2}[/tex]

Step 3:

Squaring the numbers.

[tex]d=\sqrt{16+1}[/tex]

[tex]d=\sqrt{17}[/tex]

Therefore, George's work is correct.

Option A is the correct answer.

ACCESS MORE